The transition to a democratic Portuguese judicial system: (delaying) changes in the legal culture - Dias, João Paulo (2016)
The Revolution of 25 April 1974 had a strong impact on justice in Portugal. Initially, it can be said that there was evidence of a process of democratisation involving the judicial structures, together with effective improvements to conditions allowing for independent and autonomous professional performance. However, in analysing the course of judicial reforms, it can be seen that changes took place more on a legislative level than in terms of the performance of the courts, proving that the evolution of the judicial system still demands a change of the legal culture. Therefore, the objective of this paper is to reflect on the evolution of the legal architecture in Portugal, seeking to determine whether the transition to a democratic judicial system is complete or whether, on the contrary, we are still faced with the process of justice in transition, delaying any changes in the current legal culture.